Compensating Wage Differentials, Sorting into Occupations and Job Tasks - Alexandra Fedorets (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The theory of wage premia for job disamenities exhibits mixed evidence in empirical analysis. In the current study, I employ a rich data set of workplace attributes for 1979-2012 in Germany to show that only those disagreeable workplace characteristics that are related to non-routine cognitive tasks receive a positive payoff. Moreover, sorting in occupations and job tasks explains a substantial part of both positive and negative returns to disamenities. Thus, the mixed evidence on returns to disamenitites can be explained by the type of jobs they are related to and by the magnitude by which technological progress has affected these jobs.
Keywords: J24; J28; J31; 330